Tourism Event Management System Using Gianyar Smart Tourism Based On Cloud - Pratama, I Putu Agus Eka; Wirdiani, Kadek Ayu (Journal of Electrical, Electronics and Informatics; Vol 2 No 2 (2018): JEEI (August 2018)DO - 10.24843/JEEI.2018.v02.i02.p03, 2018)
Tourism event data data in Gianyar regency must be managed well, so that it can giving knowledge to all event organizers about tourist interest of all tourism objects around Gianyar Regency. The knowledge also helping them for strategy determination and decision making. Each event organizer can manage their own tourism event data into the system and all of data can be processed to be information and report for the tourist, to make tourism service in Gianyar Regency better. This paper show the design, implementation, and testing of Tourism Event Management System using Gianyar Smart Tourism based on Cloud for all event organizers in Gianyar Regency, developed using Design Science Research Methodology (DSRM) and tested using User Accepted Testing (UAT). It also act as Knowledge Management about tourism event data and tourist demand. Conclusion, all tourism event can be managed well and all event organizers can manage their tourism event data easier.